THE EPISTOLARY WEBS OF JOSÉ ENRIQUE RODÓ AS A TESTIMONY OF THE REVISTA NACIONAL DE LITERATURA Y CIENCIAS SOCIALES (1895-1897) - da Silva Santos, Elisângela [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
In this article we aim to revisit a key moment in the epistolary dialogue of the Uruguayan thinker José Enrique Rodó (1871-1917): the interregnum 1895-1897, a period in which the work of the then young writer was turned to the editorial project of the Revista Nacional de Literatura y Ciencias Sociales. By placing Rodó at the epicenter of the relationship web built around the missives and the Revista Nacional, we will analyze how the correspondences received by him, kept in his Archive, can be read as legitimizers of his trajectory in the pedagogical exercise of literary criticism, and at the same time, they reveal his performance as an intellectual power for authors from different parts of the continent, interested in sharing ideas and projects in favor of the production of knowledge about Latin America at that time.
AS TEIAS EPISTOLARES DE JOSÉ ENRIQUE RODÓ COMO TESTEMUNHO DA REVISTA NACIONAL DE LITERATURA Y CIENCIAS SOCIALES (1895-1897)
Keywords: archive; correspondences; José Enrique Rodó; Latin America; Revista Nacional de Literatura y Ciencias Sociales